1997
DOI: 10.1046/j.1469-0705.1997.10020112.x
|View full text |Cite
|
Sign up to set email alerts
|

Reference resistance indices of the umbilical, fetal middle cerebral and uterine arteries at 24–42 weeks of gestation

Abstract: The objective of this cross-sectional study was to construct new reference ranges for Doppler flow velocity waveform resistance indices for the fetal umbilical artery, middle cerebral artery, placental and non-placental uterine arteries and the placentocerebral ratio in a large and minimally selected population attending a single clinic. Study design and data analysis adhered to a number of stringent and validated methodological recommendations derived both from the recent literature and from a review of earli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
122
4
6

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(148 citation statements)
references
References 0 publications
16
122
4
6
Order By: Relevance
“…Kurmanavicius et al [2] in their study had mentioned a dynamic behavior of the MCA RI. They observed a parabolic pattern of change in the MCA RI with increasing age; this implies that a single cut-off value should not be employed for prediction of IUGR.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Kurmanavicius et al [2] in their study had mentioned a dynamic behavior of the MCA RI. They observed a parabolic pattern of change in the MCA RI with increasing age; this implies that a single cut-off value should not be employed for prediction of IUGR.…”
Section: Discussionmentioning
confidence: 95%
“…The cutoff value of the UA resistance index was taken as 0.72. This was according to the reference value of Kurmanavicius et al [2]. The value of UA RI [0.72 was taken as an indicator of IUGR and a value B0.72 was taken as normal; for the MCA, the cut-off value of MCA PI was taken as 1.5.…”
Section: Methodsmentioning
confidence: 99%
“…4 Similar to our findings, Ozeren et al also found that though cerebroumbilical PI ratio was higher in patients with preeclampsia, but had a lower sensitivity and diagnostic accuracy to predict adverse perinatal outcome. 11 Lakhar et al also found that umbilical artery PI is more sensitive than cerebroumbilical PI ratio in predicting adverse perinatal outcome. 14 …”
Section: Discussionmentioning
confidence: 98%
“…MCA-RI was considered abnormal if measurement was 2 SD below the mean. 11 All the ultrasound evaluations were done by a single obstetrician with expertise in Doppler sonography. The intrapartum management of the women and the mode of the delivery were as per the hospital protocol.…”
Section: Methodsmentioning
confidence: 99%
“…16 They found that abnormal umbilical Doppler is associated with lower birth weight, lower APGAR score, and significant neonatal morbidity. Sensitivity of absent end diastolic flow was 100%.…”
mentioning
confidence: 99%